2021
DOI: 10.1523/jneurosci.2599-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Medial Prefrontal Cortex Has a Causal Role in Selectively Enhanced Consolidation of Emotional Memories after a 24-Hour Delay: A TBS Study

Abstract: Previous research points to an association between retrieval-related activity in the medial prefrontal cortex (mPFC) and preservation of emotional information compared with co-occurring neutral information following sleep. Although the role of the mPFC in emotional memory likely begins at encoding, little research has examined how mPFC activity during encoding interacts with consolidation processes to enhance emotional memory. This issue was addressed in the present study using transcranial magnetic stimulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…Negative emotions can enhance both the accuracy (Kensinger, 2007;Mather and Sutherland, 2011) and/or subjective feelings of vividness or confidence for retrieved memory (Dougal and Rotello, 2007;Phelps and Sharot, 2008). Previous studies observed higher sensitivity in recalling negative vs. neutral images (Anderson et al, 2006;Rimmele et al, 2011;Xie and Zhang, 2017;Yeh et al, 2021). Here, we did not observe a significant difference in sensitivity in recalling negative vs. neutral images.…”
Section: Negative Emotional Memorycontrasting
confidence: 81%
See 1 more Smart Citation
“…Negative emotions can enhance both the accuracy (Kensinger, 2007;Mather and Sutherland, 2011) and/or subjective feelings of vividness or confidence for retrieved memory (Dougal and Rotello, 2007;Phelps and Sharot, 2008). Previous studies observed higher sensitivity in recalling negative vs. neutral images (Anderson et al, 2006;Rimmele et al, 2011;Xie and Zhang, 2017;Yeh et al, 2021). Here, we did not observe a significant difference in sensitivity in recalling negative vs. neutral images.…”
Section: Negative Emotional Memorycontrasting
confidence: 81%
“…On the other hand, we observed higher reporting bias in recalling negative vs. neutral images. Indeed, while recollection was more accurate for negative than neutral scenes (Anderson et al, 2006;Yeh et al, 2021), Rimmele et al noted enhanced subjective feeling of remembering negative vs. neutral scenes without actually remembering the scene details (Rimmele et al, 2011). The other study noted item memory as enhanced under negative vs. neutral conditions was also associated with elevated subjective feelings of remembering the conditions (Xie and Zhang, 2017).…”
Section: Negative Emotional Memorymentioning
confidence: 97%
“…Negative emotions can enhance both the accuracy ( Kensinger, 2007 ; Mather and Sutherland, 2011 ) and/or subjective feelings of vividness or confidence for retrieved memory ( Dougal and Rotello, 2007 ; Phelps and Sharot, 2008 ). Previous studies observed higher sensitivity in recalling negative versus neutral images ( Anderson et al, 2006 ; Rimmele et al, 2011 ; Xie and Zhang, 2017 ; Yeh et al, 2021 ). Here, we did not observe a significant difference in sensitivity in recalling negative versus neutral images.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, intensified transcranial direct current stimulation (tDCS) targeting the mPFC has been found to improve cognitive control, motivation, and emotional functions for social anxiety disorder by modulating the amygdala–frontal network [ 62 ]. Repetitive TMS (rTMS) of the mPFC has been found to facilitate emotional memories within an emotion–cognition network, including changes in hippocampus/amygdala-mPFC circuits [ 63 ]. Collectively, the mPFC may be a promising neuromodulation target to improve memory and affective disorders.…”
Section: Discussionmentioning
confidence: 99%